MODEL KEBIJAKAN HUKUM DESENTRALISASI PENGELOLAAN LINGKUNGAN HIDUP BERBASIS PENDEKATAN EKOSISTEM - Akib, Muhammad (FIAT JUSTISIA)
Conceptually, policies of environmental decentralization aims to environmental conditions will be better. But the reality since the enactment of Act No. 22 of 1999 (now replaced by Act No. 32 of 2004) environmental damage tends to increase. This study aims to find a model appropriate legal policy in environmental management. The method used depart from the doctrinal legal research, which is reviewing all legal product both at national and local levels Lampung related to environmental management. As a complement to use socio-legal method. The results of this research show that the legal policy of decentralization is not reflecting the ecosystem approach, among other because of the strong interest of the sector, the domination of economic interests, and the weakness of good governance. The ideal legal policy model is to combines aspects of democratization and the sustainability of ecosystems. This model is implemented in the division of authority, institutional capacity of the environment and interregional cooperation